2003
DOI: 10.1046/j.1525-1497.2003.20821.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving the physical diagnosis skills of third-year medical students

Abstract: This physical diagnosis curriculum was successful in improving students' knowledge, skill, and self-confidence in physical diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…These results are further supported by the moderate effect sizes achieved by the intervention group in the musculoskeletal and GI stations, suggesting that the differences found between groups have clinical significance. We believe these differences are a reflection of the directed bedside teaching intervention and are consistent with the findings of others demonstrating the benefits of dedicated instruction in physical examination skills, either at the bedside or in a setting with standardized patients (Fagan et al 2003;Fox et al 2001;Gale and Gale 2006;Junger et al 2005;Schwind et al 2001). Students were randomly assigned to the medicine clerkship sites prior to the beginning of their 3rd year.…”
Section: Discussionsupporting
confidence: 61%
“…These results are further supported by the moderate effect sizes achieved by the intervention group in the musculoskeletal and GI stations, suggesting that the differences found between groups have clinical significance. We believe these differences are a reflection of the directed bedside teaching intervention and are consistent with the findings of others demonstrating the benefits of dedicated instruction in physical examination skills, either at the bedside or in a setting with standardized patients (Fagan et al 2003;Fox et al 2001;Gale and Gale 2006;Junger et al 2005;Schwind et al 2001). Students were randomly assigned to the medicine clerkship sites prior to the beginning of their 3rd year.…”
Section: Discussionsupporting
confidence: 61%
“…Acquired physical examination skills are known to be of lasting value. Data suggests that even greater emphasis should be placed on basic clinical skills [ 1 , 2 ]. In recent years, there has been a trend in medical curricula away from classical teacher-centred lectures towards clinical skills courses including peer physical examinations by students as well as bedside teaching.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, evidence has shown that the examination skills of medical students and clinicians have deteriorated (Mangione and Peitzman, ; Wenrich et al, ; Oliver et al, ). This is, in part, attributed to a greater reliance on improving imaging technologies and other investigation modalities to diagnose patients, (Dunnington et al, ; Macdessi and Oates, ; Bordage, ; Mangione and Peitzman, ; Tavel, ; Anderson et al, ; Fagan et al, ). Although these advancements are often critical to improving patient care, the number of unnecessary investigations performed on patients has increased, a lot of which could have been avoided by simple examination (Macdessi and Oates, ; Bordage, ).…”
Section: Introductionmentioning
confidence: 99%